Episiotomy Practice and Its Associated Factors in Africa: A Systematic Review and Meta-Analysis - Woldegeorgis, Beshada Zerfu; Obsa, Mohammed Suleiman; Tolu, Lemi Belay; Bogino, Efa Ambaw; Boda, Tesfalem Israel; Alemu, Henok Berhanu (Frontiers in Medicine, 2022)
ABSTRACT Background: Episiotomy, a surgical procedure that enlarges the vaginal opening during childbirth, was common practice until the early 2000s. Other sources, including the World Health Organization (WHO), advocate for the selective use of episiotomy. Episiotomy rates, on the other hand, have remained high in developing countries, while declining in developed countries. As a result, the current study sought to determine the overall prevalence of episiotomy in Africa as well as the risk factors associated with its practice. Methods: Articles were searched in international electronic databases. A standardized Microsoft Excel spreadsheet and STATA software version 14 were used for data extraction and analysis, respectively. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist was used to write this report. A random-effects meta-analysis model was used to determine the pooled prevalence of episiotomy. A heterogeneity test was conducted using I-Squared (I2) statistics. Egger’s test and funnel plots were conducted to detect publication bias. Subgroup analysis was also conducted. Association was expressed through a pooled odds ratio (OR) with a 95% Confidence Interval (CI). Result: A total of 21 studies with 40831 participants were included in the systematic review and meta-analysis. The pooled prevalence of episiotomy practice was 41.7 (95%CI (36.0 – 47.4), I2 = 99.3%, P < 0.001)). Primiparity (OR: 6.796 (95% CI (4.862–9.498)), P < 0.001, I2: 95.1%), medical doctors- assisted delivery (OR: 3.675 (95% CI (2.034–6.640)), P < 0.001, I2: 72.6%), prolonged second stage of labor (OR: 5.539 (95% CI (4.252–7.199)), P < 0.001, I2: 0.0%),using oxytocin (OR: 4.207 (95% CI (3.100–5.709)), P < 0.001, I2: 0.0%), instrument -assisted vaginal delivery (OR: 5.578 (95% CI (4.285–7.260)), P < 0.001, I2: 65.1%),and macrosomia (OR: 5.32(95% CI (2.738–10.339)), P< 0.001, I2: 95.1%) were factors associated with episiotomy practice . Conclusion: In this review, the prevalence of episiotomy among African parturients was high. A selective episiotomy practice should be implemented to reduce the high episiotomy rates.